5hmC modification regulates R-loop accumulation in response to stress - Xu, Xingyun; Wang, Junjie; Wang, Wenjuan; Zhang, Yutong; Wan, Bo; Miao, Zhigang; Xu, Xingshun (Frontiers in Psychiatry, 2023)
R-loop, an RNA-DNA hybrid structure, arises as a transcriptional by-product and has been implicated in DNA damage and genomic instability when excessive R-loop is accumulated. Although previous study demonstrated that R-loop is associated with ten-eleven translocation (Tet) proteins, which oxidize 5-methylcytosine to 5-hydroxymethylcytosine (5hmC), the sixth base of DNA. However, the relationship between R-loop and DNA 5hmC modification remains unclear. In this study, we found that chronic restraint stress increased R-loop accumulation and decreased 5hmC modification in the prefrontal cortex (PFC) of the stressed mice. The increase of DNA 5hmC modification by vitamin C was accompanied with the decrease of R-loop levels; on the contrary, the decrease of DNA 5hmC modification by a small compound SC-1 increased the R-loop levels, indicating that 5hmC modification inversely regulates R-loop accumulation. Further, we showed that Tet deficiency-induced reduction of DNA 5hmC promoted R-loop accumulation. In addition, Tet proteins immunoprecipitated with Non-POU domain-containing octamer-binding (NONO) proteins. The deficiency of Tet proteins or NONO increased R-loop levels, but silencing Tet proteins and NONO did not further increase the increase accumulation, suggesting that NONO and Tet proteins formed a complex to inhibit R-loop formation. It was worth noting that NONO protein levels decreased in the PFC of stressed mice with R-loop accumulation. The administration of antidepressant fluoxetine to stressed mice increased NONO protein levels, and effectively decreased R-loop accumulation and DNA damage. In conclusion, we showed that DNA 5hmC modification negatively regulates R-loop accumulation by the NONO-Tet complex under stress. Our findings provide potential therapeutic targets for depression.